An Explicit Isomorphism in R/Z-K-Homology - Elmrabty, Adnane; Maghfoul, Mohamed (Communications in Mathematics and Applications, 2014)
In this paper, we construct an explicit isomorphism between the at part of differential K-homology and the Deeley R/Z-K-homology.